The Morphology and Kinematics of a Giant, Symmetric Nebula around a Radio-loud Quasar 3C 57: Extended Rotating Gas or Biconical Outflows? - Zhuoqi (Will) Liu; Sean D. Johnson; Jennifer I-Hsiu Li; Benoît Epinat; Gwen C. Rudie; Ana Monreal-Ibero; Sebastiano Cantalupo; Zhijie Qu; Mandy C. Chen; Wolfram Kollatschny; Sowgat Muzahid; Fakhri S. Zahedy; et al. (The Astrophysical Journal)
Gas flows between galaxies and the circumgalactic medium play a crucial role in galaxy evolution. When ionized by a quasar, these gas flows can be directly traced as giant nebulae. We present a study of a giant nebula around a radio-loud quasar, 3C 57 at z  ≈ 0.672. Observations from MUSE reveal that the nebula is elongated with a major axis of 70 kpc and a minor axis of 40 kpc. The nebula displays an approximately symmetric blueshifted–redshifted pattern along the major axis and multicomponent emission features in its [O II ] and [O III ] profiles. The morphology and kinematics can be explained as rotating gas or biconical outflow, both of which qualitatively reproduce the observed position–velocity diagram. The 3C 57 nebula is significantly more kinematically disturbed, with W _80 (the line width encompassing 80% of the flux) of approximately 300–400 km s ^−1 , compared to H i gas in local early-type galaxies, which typically shows W _80  ≈ 50 km s ^−1 . This velocity dispersion is comparable to the gas in cool-core clusters despite originating in a group 100 times less massive. For biconical outflow models, the inferred 10°–20° inclination angle is in tension with the unobscured nature of the quasar, as the dusty torus is expected to be perpendicular to the outflow. Neither a quiescent rotating gas origin nor an biconical outflow fully reproduces the observed kinematics and morphology of the 3C 57 nebula, suggesting a more intricate origin likely involving both rotation and active galactic nuclei feedback.